Hellenism in Captivity and “Neo-Hellenic” Nations: The Resilience of the Byzantine Identity after the Fall of Constantinople - Efstathios Lianos-Liantis; George Kalpadakis (European Journal of History and Culture, 2024)
The Byzantine Commonwealth stands out in the annals of history as an indelible construct which exercised a profound influence on the preservation and continual reinvigoration of the Greek cultural heritage. Functioning as the custodian of ancient Greek legacies, it served as a bulwark against the tides of time and also facilitated the dissemination of these cultural elements to the burgeoning civilizations of the Medieval Age. As the ultimate bastion of the Hellenistic tradition, the Commonwealth evolved into a “crucible”, wherein profound Christian theological inquiries flourished, thus laying the groundwork for an authentically ecumenical Orthodoxy. This epochal transformation served as the cornerstone for the delineation of the spiritual and intellectual contours that came to define the Eastern world in its entirety. Hellenism served not only as a cultural foundation but also as a dynamic force in fostering national consciousness and resistance against conquering powers. In the end, the resilience of Byzantine culture contributed significantly to the formation of modern Neo-Hellenic/Neo-Byzantine identities, influencing contemporary sociopolitical movements and policies. This paper offers a review of key historical events and philosophical shifts which defined this long process and shaped the development of modern East European nations. It also highlights the complex interplay between historical heritage and modern national identity